PENGARUH KEPEMILIKAN MANAJERIAL DAN PROPORSI KOMISARIS INDEPENDEN TERHADAP KUALITAS LABA DENGAN KEPEMILIKAN PENGENDALI SEBAGAI VARIABEL MODERASI - Khair, Ummul; Kamaluddin, Kamaluddin; Suranta, Eddy (JURNAL FAIRNESS, 2015)
Ownership structure is very important because it is closely related to the operational control of the company. From the point of view of the theory of accounting, earnings management is determined by the motivation of the company manager. Different motivations will result in a different amount of earning management, such as the manager who also shareholders of the company with a manager who is not a shareholder and board composition also plays an important role in control of what is done by the executive or the board of directors as well as monitoring the effectiveness of the board of commissioners are affected by some degree of ownership concentration, and the relationship between managerial ownership with earnings quality is interaction by ownership concentration. This study aimed to determine the effect of managerial ownership on earnings quality, the proportion of independent directors on the quality of earnings, the interaction between managerial stock ownership by the controlling stake of the quality of earnings and the interaction between the proportion of independent directors with a controlling stake of the quality of earnings. The research sample using companies listed in Indonesia Stock Exchangein 2009-2011. “The technique of purposive sampling method. “These result indicate that managerial ownership has a negative effect on the quality of earnings, proportion of independent directors has a positive effect on the quality of earnings, the interaction between managerial stock ownership with no controlling shareholding positive effect on earnings and the quality of interaction between the proportion of independent directors with a controlling shareholding positive effect on earnings quality .